Entrepreneurship - Hisrich,Robert D (McGraw Hill Education, 2013)
Entrepreneurship, by Hisrich, Peters and Shepherd is intended for the undergraduate and graduate courses in entrepreneurship and has been designed to instruct students on how to formulate, plan, and implement a new venture. Students are exposed to detailed descriptions of 'how to' embark on a new venture in a logical manner. Actual case studies and entrepreneur profiles help illustrate successful and not-so-successful ventures.